Can Legal Orders Emerge Without Independent Norms? The Case of the Consensual Secession - Baquerizo Minuche, Jorge (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
According to some well-known conceptual elaborations within the theory of law, every legal order emerges through the production of «independent» norms, i.e., norms that lack any identifiable basis of validity in legal norms. However, some authors consider that this is neither a necessary nor a sufficient condition for the emergence of a new legal order: in cases of consensual secession, for instance, a new legal order would emerge without unauthorized norms. In this paper I will analyze and criticize this last idea and conclude that, even with the possibility of a successful consensual secession, the existence of a new legal order does not follow per se. This can only occur under a necessary condition: to produce «independent» norms.